0473 Effectiveness and Safety of Lemborexant in Subjects Previously Treated with Placebo for 6 Months in SUNRISE-2. (27th May 2020) - Yardley, J; Inoue, Y; Pinner, K; Perdomo, C; Filippov, G; Kubota, N; Moline, M
Abstract: Introduction: In SUNRISE-2 (NCT02952820; E2006-G000-303), while lemborexant (LEM) provided significant benefit versus placebo (PBO) on sleep-diary measurements over 6mo, some improvement was noted in PBO subjects. We report outcomes from PBO subjects rerandomized to LEM during the last 6mo of SUNRISE-2. Methods: SUNRISE-2 was a randomized, double-blind, global phase 3 study in adults (≥18y) with insomnia disorder. Subjects received PBO or LEM (5mg [LEM5]; 10mg [LEM10]) for 6mo. PBO subjects were rerandomized to LEM for another 6mo; LEM subjects continued assigned treatment. Changes from 6mo baseline (calculated after PBO completion) in subjective sleep onset latency (sSOL), subjective sleep efficiency (sSE), and subjective wake after sleep onset (sWASO) are reported for rerandomized subjects. Results: At study baseline for PBO subjects (n=318), median sSOL (min) was 55.9, mean (SD) sSE (%) and sWASO (min) were 61.3 (17.8) and 132.5 (80.2), respectively. The 6mo baseline values for rerandomized PBO-LEM5 (n=133) and PBO-LEM10 (n=125) subjects, respectively, were: median sSOL, 31.2, 34.3; mean (SD) sSE, 70.5 (20.2), 71.1 (18.0); mean (SD) sWASO, 105.1 (80.6), 100.1 (84.6). Median sSOL decreased from the 6mo baseline after 1mo (PBO-LEM5, −3.2; PBO-LEM10, −2.9) and 6mo (PBO-LEM5, −2.7; PBO-LEM10, −5.0). Mean (SD) sSE increased from the 6mo baseline after 1mo (PBO-LEM5, 3.9 [12.1]; PBO-LEM10, 3.5 [8.1]) and 6mo (PBO-LEM5, 3.9 [13.6]; PBO-LEM10, 4.5 [13.0]). Mean (SD) sWASO decreased after 1mo (PBO-LEM5, −8.5 [49.4]; PBO-LEM10, −5.7 [36.1]) and 6mo (PBO-LEM5, −8.2 [49.0]; PBO-LEM10, −10.0 [58.8]). Treatment-emergent adverse events incidence was similar during PBO (62.7%) and LEM treatment (PBO-LEM5, 54.9%; PBO-LEM10, 57.7%). Adverse events were consistent with those seen in the initial 6mo of treatment for patients originally randomized to LEM. Conclusion: Rerandomization to LEM was associated with additional improvement in sleep outcomes following the PBO-related response. LEM benefit was evident after 1mo and was sustained throughout treatment. LEM was well tolerated. Support: Eisai Inc.